Determining the definition and components of successful soccer referee performance - Westbrooks, J.; Low, D. A.; Brownlee, T. E. (Journal of Sports Sciences, 2023)
There has been little work examining the intricacies of what makes a soccer referee successful. The aim of this study was to determine what the definition of a successful referee performance is and what are the characteristics of a successful referee from a broad range of stakeholders in Major League Soccer (MLS) and the Professional Referees Organisation (PRO). The study used Delphi methodology to ask 6 MLS General Managers, 2 MLS Coaches,1 MLS League Officer, 4 PRO Referees and 10 PRO Assistant Referees, 8 PRO Staff and 5 PRO Assessors, and 2 PRO2 Referees two questions: 1. Their definition of a successful referee performance. 2. Their opinion on the characteristics of a successful referee. The result was a 7-point definition of a successful referee performance and 26 characteristics of a successful referee. There were ten characteristics that overlapped with previous work examining successful referees. This study was able to develop a definition of a successful referee performance and determine the characteristics of a successful referee.